Occurrence of macrolides resistance in Legionella pneumophila ST188: Results of the Belgian epidemiology and resistome investigation of clinical isolates - Charlotte Michel; Fedoua Echahidi; Geraldine De Muylder; Max Sewell; Ian Boostrom; Olivier Denis; Owen B. Spiller; Denis Pierard (International Journal of Infectious Diseases)
Objectives: The incidence of Legionnaires’ disease steadily increases worldwide. Although Legionella pneumophila is known as pathogenic, systematic investigations into antibiotic resistance are scarce, and reports of resistance in isolates are recently emerging. Methods: Clinical cases and metadata reported to the Belgian National Reference Centre between 2011 and 2022 were retrospectively analyzed. A total of 283 clinical isolates were typed by core genome multi-locus sequence typing (cgMLST). Acquired genes or mutations triggering resistance were extracted from all of them. Results: The number of Legionnaires’ disease cases has increased in Belgium. Urinary antigen testing remains the main used test, but polymerase chain reaction and serology allow the diagnostic in 14.8% and 2.4% of cases, respectively. cgMLST showed a good discrimination between sequence typing (ST) and minimal variation for ST47 isolates, whereas ST1s were more diverse. Genotypic screening identified a 23S ribosomal RNA mutation linked to a high-level macrolide resistance in one isolate of ST188, which is genetically closed to resistant isolates from France. Conclusion: The increase in incidence is of concern and likely an under-estimate due to the reliance on urine antigen testing. Routine typing by cgMLST allows good discrimination and the first clinical isolate reported as resistant for macrolides was cultured, underscoring the need to define resistance breakpoints and incorporate antimicrobial susceptibility testing as routine clinical investigation practice.